Comparison of Side Effects of General Anesthesia and Spinal Anesthesia in Postoperative Patients - Kurnia, Dedi; Setiawan, Sartono (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Anesthesia is an action to relieve pain during surgery and various other procedures that cause pain in the body, there are several anesthesia actions including general and spinal anesthesia but the anesthesia action causes some side effects. Objective: This study aims to determine the comparison of side effects of spinal anesthesia and general anesthesia in postoperative patients. Method: The research design used in this study is a comparative study with the type of descriptive research. Population The population in this study was patients under spinal anesthesia and general anesthesia. Result and Discussion: Based on the results of statistical analysis of the Chi-square test, it shows that there is a significant comparison in both types of anesthesia used for surgery, namely general narcose anesthesia and spinal anesthesia on postoperative side effects with a value of (p-value = 0.026).  Conclusion: The conclusion of two different types of anesthesia shows significant differences due to differences in the way of administration of anesthetic drugs and the doses given so that they get different side effects. Advice in using the type of anesthesia must be considered the type of surgery to be performed as little as possible must reduce the side effects obtained by the patient.